IMPLIKATUR PERCAKAPAN TERHADAP SISWA PELANGGAR ATURAN SEKOLAH (KAJIAN LINGUISTIK FORENSIK INTEROGASI) - Karmila Indah Hasin; Johar Amir; Juanda Juanda (Universitas Negeri Makassar, 2020)
Implications of Conversations for Students Violating School Rules (Interrogation Forensic Linguistics Study). This research describes the phenomena of students' language and the form of conversational implicature using forensic linguistic studies. This research uses the principle of cooperation Grice. The violation of the principle of cooperation as an effort to defend students to cover up mistakes. This is the main attraction in pragmatic research on legal cases. Pressing speech causes uncomfortable speech partners, so they choose to avoid conversations by providing convoluted information. Speeches that utilize the principles of conversation in pragmatic theory produce interrogation language patterns that can be used to obtain information.